PENGARUH EDUKASI GIZI MENGGUNAKAN MEDIA LEAFLET DAN VIDEO TERHADAP PENINGKATAN PENGETAHUAN GIZI SEIMBANG PADA REMAJA DI SMA NEGERI 2 LINTONGNIHUTA - Miranda Andaresta Manullang (2022)
Adolescence is a transition period from children to adults and adolescence experiences rapid growth and development so that it requires optimal nutrition. A healthy teenager is a teenager who has a good and balanced nutritional status. Knowledge can influence adolescent attitudes in consuming balanced nutritional foods. The purpose of this research is to increase the knowledge of adolescents regarding balanced nutrition using leaflets and videos in the hope that adolescents can change attitudes and practices of adolescents to pay more attention to nutritional status and consume foods with balanced nutrition according to their individual needs. This study uses a quasi-experimental method with a pretest-post test two group design. The selected sample is 46 people aged 16-18 years. Data collection and collection were carried out using leaflets, videos, and questionnaires. The data obtained were tested using the T test. The results showed that there was an increase in knowledge of balanced nutrition after providing nutrition education using leaflets and videos (p value 0.000). The results of the independent T test showed no significant difference related to the effectiveness of leaflet and video media (p-value 0.197).